2018
DOI: 10.1002/pds.4449
|View full text |Cite
|
Sign up to set email alerts
|

Imposed registries within the European postmarketing surveillance system: Extended analysis and lessons learned for regulators

Abstract: Purpose: Building on previous research, we examined whether delayed study start and low patient accrual rates found in 31 postauthorization registry-based studies requested by European Medicines Agency (EMA) are maintained after 2 additional years of follow-up. Method:The registries identified in the previous EMA study and the same methodology were used. The follow-up was extended from June 2015 to November 2017.The information available for the following variables was updated: marketing authorization status, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Notwithstanding such potential, the under-use of patient registries in the regulatory context is striking [10, 11]. Of 335 products recommended for approval between 2005 and 2013 by the main scientific committee of the European Medicines Agency (EMA), the Committee for Medicinal Products for Human Use (CHMP), 31 registries were requested to fulfil a condition of the marketing authorisation, but by December 2017, just ten had been completed [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding such potential, the under-use of patient registries in the regulatory context is striking [10, 11]. Of 335 products recommended for approval between 2005 and 2013 by the main scientific committee of the European Medicines Agency (EMA), the Committee for Medicinal Products for Human Use (CHMP), 31 registries were requested to fulfil a condition of the marketing authorisation, but by December 2017, just ten had been completed [11].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding such potential, the under-use of patient registries in the regulatory context is striking [10, 11]. Of 335 products recommended for approval between 2005 and 2013 by the main scientific committee of the European Medicines Agency (EMA), the Committee for Medicinal Products for Human Use (CHMP), 31 registries were requested to fulfil a condition of the marketing authorisation, but by December 2017, just ten had been completed [11]. Potentially, registries could provide data permitting comparisons of outcomes from different treatments across different countries and healthcare settings over time as well as assessment of the impact of measures taken to minimise risks of medicinal products [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…A predecessor to this study by Bouvy et al found that for 392 products that received a positive CHMP opinion from 2005-2013, there were 31 registries that were requested for 30 products (7.7%) in total (65% were product registries, 35% were disease registries) with 71% having a primary safety objective. 15,16 This frequent use of product registries led to the establishment of the EMA Patient Registry initiative supporting the use of existing patient registries for the postauthorization benefit-risk monitoring of medicinal products. 17 This was subsequently followed up with proposals for operational methods for increasing the use of patient registries in medicines regulation by addressing: the nature of the data collected and registry quality assurance processes; registry governance, informed consent, data protection, and sharing; and stakeholder communication and planning of benefit-risk assessments.…”
Section: Discussionmentioning
confidence: 99%
“…EU analyses of postauthorisation safety studies, and the use of registries are also available 21–25 . A review of EU centrally approved products between 2005–2013 indicated that EMA imposed PLEG through a registry in 4 and 29% of nonorphan and orphan medicinal products, respectively, and in 12 and 67% of products licensed under conditional or exceptional routes, respectively 21 .…”
Section: Pleg Characteristicsmentioning
confidence: 99%